The impact of mentor support and high-quality connections on student teachers’ psychological safety and engagement during practicum - Dreer-Goethe, Benjamin (Frontiers in Education, 2025)
IntroductionTeaching is a social profession, and learning to become a teacher involves social interactions. Previous research has predominantly focused on the role of mentor support when investigating the social support of student teachers during field experiences in teacher education. Much less attention has been paid to the social interactions that take place outside the mentor pairing between student teachers and other co-workers at practicum schools.MethodsIn this study, a longitudinal design was implemented to investigate how the experiences of mentor support and of high-quality connections outside the mentor–mentee pairing contributed to the psychological safety and engagement of 156 German student teachers during their practicum.ResultsThe results show that social support from mentors predicts the engagement (β = 0.22) and psychological safety (β = 0.25) of student teachers to a similar extent. Furthermore, the analyses reveal that experiencing high-quality connections with school colleagues is equally associated with engagement (β = 0.20). With a larger effect (β = 0.44), the experience of high-quality connections predicts the psychological safety of student teachers. These findings suggest that creating a secure social foundation for the professional development of student teachers requires not only a dedicated mentor but also active involvement of the school staff.DiscussionThis research offers new insights into the impact of social connections within and beyond the mentor-mentee relationship, addressing a notable gap in previous studies that mainly focused on the mentor-mentee connection.